Ultrasound biomicroscopy evaluation of anterior extension in retinoblastoma: a clinicopathological study. Issue 3 (23rd May 2011) - Moulin, Alexandre P; Gaillard, Marie-Claire; Balmer, Aubin; Munier, Francis L
Abstract : Background: Extension of retinoblastoma cells into the posterior chamber is a criterion for group E according to the international classification of intraocular retinoblastoma. Currently, the anterior extension of retinoblastoma is based on the presence of tumour cells in the anterior chamber assessed by biomicroscopy. Aim: To determine the value of ultrasound biomicroscopy (UBM) in the assessment of posterior chamber involvement in advanced retinoblastoma. Methods: Retrospective review of all retinoblastoma cases enucleated at the Jules Gonin Eye Hospital from January 1996 to December 2009 for which UBM (35 MHz) evaluation was available. The patients' records were reviewed for patient and tumour features and histopathological findings. UBM findings were compared with histopathological features. Results: UBM documentation was available in 31 cases. Retinoblastoma was detected by UBM in the posterior chamber in 18 cases and was absent in 13 cases while histopathological analysis demonstrated its presence in the posterior chamber in 22 cases and its absence in 9 cases. Among the 18 UBM-positive cases, 7 had biomicroscopic detectable involvement of the anterior chamber. There was a significant correlation between echodensities consistent with retinoblastoma on UBM in the posterior chamber and histopathological tumorous involvement of the posterior chamber (p=0.0001). The sensitivity of UBM in the assessment of posterior chamber invasion by retinoblastoma was 81% and the specificity was 100%. Conclusion: In selected cases of advanced retinoblastoma, UBM appears to represent a valuable tool in the precise evaluation of anterior extension of disease, with good sensitivity and specificity for the assessment of posterior chamber involvement. UBM may provide useful criteria governing the indication for enucleation.